2023
DOI: 10.1177/10598405221150879
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Mental Health and Well-Being of School Nurses After the First Wave of the COVID-19 Pandemic: A National Cross-Sectional Survey

Abstract: The aim of this study was to examine the associations between job stressors, COVID-19-related concerns, burnout, and mental health and well-being among school nurses, and whether any of these associations are mediated by burnout. Based on stratified proportional sampling, data collection was conducted by an online questionnaire distributed to 600 school nurses in Taiwan. A total of 256 participants aged between 27 and 62 years (mean = 47.08; standard deviation = 7.28) returned questionnaires. Results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…School nurses were faced with the novel tasks of protecting the health of the school community without adequate training or consistent guidance. Workload was already a burden, and the lack of additional human resources to conduct case management and contact tracing affected school nurse mental well-being during the pandemic (Chen et al, 2023).…”
Section: The State Of School Staff Well-beingmentioning
confidence: 99%
“…School nurses were faced with the novel tasks of protecting the health of the school community without adequate training or consistent guidance. Workload was already a burden, and the lack of additional human resources to conduct case management and contact tracing affected school nurse mental well-being during the pandemic (Chen et al, 2023).…”
Section: The State Of School Staff Well-beingmentioning
confidence: 99%
“…In 2022, the Job Stress Index showed that the proportion of the Swiss professionally active who feel emotionally exhausted exceeded 30% (16). Indeed, since the COVID-19 pandemic, burnout is reported at unprecedented rates in all countries (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Since the breakout of COVID-19 pandemic, physicians have been reporting burnout in all medical specialties at unprecedented rates ( 16 ). However, it has also been affecting mental health of other front-line or essential workers ( 17 , 18 , 19 , 20 , 21 ) and all workers in general. By aggravating mental health determinants in the working and living environment, the COVID-19 crisis triggered a 27.6 % increase in the incidence of major depressive disorder globally ( 22 ).…”
mentioning
confidence: 99%